História e memória do terreiro Axé Ilê Obá - Correa, Renato Pereira (2014)
The objective of this research is to rescue the history of terreiro Axé ilê Obá. For the analysis we use political, social and economic aspects, the basis for the understanding of possible ruptures and continuities. The study of memory from the life stories of those involved has privileged lived. Therefore, the articulation in areas besides religion by the current religious leadership, 'Mother' Sylvia of Oxalá, provided the historical stumbling of the terreiro, guaranteeing the continuity and consolidation of the territory as a place of collective sociability. Despite segregationist and racist policies structured in the postabolition affecting blacks territories, we concentrate on the movement of the terreiro by the city and how it became a place of reference for the african-Brazilian culture in São Paulo